From Simplicity to Sustainability: Structuring Minimalist Housing with SDG Metrics - Yildiz, Duygu; Markoc, Ilkim (MDPI, 2025)
The increasing construction-driven growth in urbanization requires innovative and holistic design approaches for sustainable housing. This study examines the relationship between Minimalist Design Principles (MDPs) and the UN SDGs and develops a multi-stage decision-support model to operationalize these links. The research adopts a five-stage mixed-methods design. It includes content analysis based on a systematic literature review, conceptual mapping, a two-round Delphi method (N = 56), Fuzzy AHP for criteria weighting, and SEM for model validation. A total of 13 MDPs were mapped against 17 SDGs and 169 subtargets, revealing particularly strong linkages with SDG 11 (Sustainable Cities and Communities) and SDG 12 (Responsible Consumption and Production). The SEM results confirm the structural validity of the proposed model. Among the minimalist principles, those associated with resource, material, and process simplification and user needs, functional flexibility, and quality of life emerged as the most influential factors for the SDGs. This study proposes a measurable, multidimensional decision-support model in sustainable architecture that clarifies how MDPs influence the SDGs.
Keywords: minimalism; sustainable development goals; housing production; Delphi technique; CONSTRUCTION; Science & Technology - Other Topics; Environmental Sciences & Ecology